Hummingbirds of Texas : with Their New Mexico and Arizona Ranges - Shackelford, Clifford Eugene, 1967- (Book collections on Project MUSE., 2009)
Written for a general audience, with spectacular images for birders and nature enthusiasts at every level, Hummingbirds of Texas: With Their New Mexico and Arizona Ranges reveals the enormous appeal of this tiniest and shiniest of birds. The book opens with a look at the many manifestations of the human attraction to these flying jewels, including the Hummingbird Roundup, a citizen-science project run by the Texas Parks and Wildlife Department, as well as the Rockport Fulton Hummer/Bird Celebration, one of several festivals dedicated to hummingbirds. The book also includes easy tips for attracting hummingbirds to your own lawn or garden, such as what to plant in the ground or in pots and how to choose and take care of feeders. The authors then showcase the nineteen different hummingbird species that have appeared in the region covered by the book. Magnificent color photographs and original artwork aid in identification and accompany descriptions, range maps, and abundance graphs for each species.